Two New Records of Orchids from Dehra Dun - Deva, Som (Indian Forester, 1969)
Two terrestrial orchids, Nervilia infundibulifolia Blatt. and McC. and N. monantha Blatt. and McC., reported to be occurring only in Western India, have now been recorded from Debra Dun in North India.